Scientific Opinion on the safety and efficacy of Scansmoke SEF7525 (smoke flavourings) for cats and dogs - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal)
Abstract Scansmoke SEF7525 is intended to provide a smoke flavour in feed for cats and dogs. It is based on extracts from the condensation products of the combustion of wood. This type of product is primarily defined by the manufacturing process and the mix of woods from which it derives. Consequently the conclusions below apply only to Scansmoke SEF7525 and cannot be extrapolated to other smoke flavours. The FEEDAP Panel concludes that a concentration of 40 mg/kg complete feed would be safe for both dogs and cats. No specific data on safety for the user was provided. The FEEDAP Panel considers it prudent to treat the product under assessment as irritant to skin, eye and respiratory tract, a skin sensitiser and harmful if swallowed. Since this mixture is used in food as smoke flavour, and its function in feed is essentially the same as that in food no further demonstration of efficacy is necessary.